A ubiquitous endocrine disruptor tributyltin induces muscle wasting and retards muscle regeneration. Issue 1 (16th November 2022) - Chiu, Hsien‐Chun; Yang, Rong‐Sen; Weng, Te‐I; Chiu, Chen‐Yuan; Lan, Kuo‐Cheng; Liu, Shing‐Hwa
Abstract: Background: Organotin pollutant tributyltin (TBT) is an environmental endocrine disrupting chemical and is a known obesogen and diabetogen. TBT can be detected in human following consumption of contaminated seafood or water. The decrease in muscle strength and quality has been shown to be associated with type 2 diabetes in older adults. However, the adverse effects of TBT on the muscle mass and function still remain unclear. Here, we investigated the effects and molecule mechanisms of low‐dose TBT on skeletal muscle regeneration and atrophy/wasting using the cultured skeletal muscle cell and adult mouse models. Methods: The mouse myoblasts (C2C12) and differentiated myotubes were used to assess the in vitro effects of low‐dose tributyltin (0.01–0.5 μM). The in vivo effects of TBT at the doses of 5 and 25 μg/kg/day ( n  = 6/group), which were five times lower than the established no observed adverse effect level (NOAEL) and equal to NOAEL, respectively, by oral administration for 4 weeks on muscle wasting and muscle regeneration were evaluated in a mouse model with or without glycerol‐induced muscle injury/regeneration. Results: TBT reduced myogenic differentiation in myoblasts (myotube with 6–10 nuclei: 53.9 and 35.8% control for 0.05 and 0.1 μM, respectively, n  = 4, P  < 0.05). TBT also decreased myotube diameter, upregulated protein expression levels of muscle‐specific ubiquitin ligases (Atrogin‐1 and MuRF1), myostatin, phosphorylated AMPKα, and phosphorylated NFκB‐p65, and downregulated protein expression levels of phosphorylated AKT and phosphorylated FoxO1 in myotubes (0.2 and 0.5 μM, n  = 6, P  < 0.05). Exposure of TBT in mice elevated body weight, decreased muscle mass, and induced muscular dysfunction (5 and 25 μg/kg, P  > 0.05 and P  < 0.05, respectively, n  = 6). TBT inhibited soleus muscle regeneration in mice with glycerol‐induced muscle injury (5 and 25 μg/kg, P  > 0.05 and P  < 0.05, respectively, n = 6). TBT upregulated protein expression levels of Atrogin‐1, MuRF1, myostatin, and phosphorylated AMPKα and downregulated protein expression level of phosphorylated FoxO1 in the mouse soleus muscles (5 and 25 μg/kg, P  > 0.05 and P  < 0.05, respectively, n  = 6). Conclusions: This study demonstrates for the first time that low‐dose TBT significantly inhibits myogenic differentiation and triggers myotube atrophy in a cell model and significantly decreases muscle regeneration and muscle mass and function in a mouse model. These findings suggest that low‐dose TBT exposure may be an environmental risk factor for muscle regeneration inhibition, atrophy/wasting, and disease‐related myopathy.